2020
DOI: 10.3390/cancers12010222
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Aggressive Clinical T1 Stage Clear Cell Renal Cell Carcinoma for Identifying Potential Diagnostic and Prognostic Biomarkers

Abstract: The molecular characteristics of early-stage clear cell renal cell carcinomas (ccRCCs) measuring ≤7 cm associated with poor clinical outcomes remain poorly understood. Here, we sought to validate genes associated with ccRCC progression and identify candidate genes to predict ccRCC aggressiveness. From among 1069 nephrectomies performed on patients, RNA sequencing was performed for 12 ccRCC patients with aggressive characteristics and matched pairs of 12 ccRCC patients without aggressive characteristics. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Our previous studies have demonstrated that forkhead box protein C2 (FOXC2) and cytoskeleton-associated, protein-glycine (CAP-Gly)-rich, domain-containing linker protein family member 4 (CLIP4) mutations were associated with early-stage ccRCC, and a synchronous metastasis [10] and validation study confirmed that PBRM1, BAP1, and FOXC2 were shown to be significantly associated with aggressive early-stage ccRCC through target sequencing and immunohistochemistry [5]. In our latest study, we have identified new candidate genes (AQP1, DDX11, BAIAP2L1, and TMEM38B) by RNA sequencing of formalin-fixed, paraffin-embedded tissues and validating in frozen tissues [11].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our previous studies have demonstrated that forkhead box protein C2 (FOXC2) and cytoskeleton-associated, protein-glycine (CAP-Gly)-rich, domain-containing linker protein family member 4 (CLIP4) mutations were associated with early-stage ccRCC, and a synchronous metastasis [10] and validation study confirmed that PBRM1, BAP1, and FOXC2 were shown to be significantly associated with aggressive early-stage ccRCC through target sequencing and immunohistochemistry [5]. In our latest study, we have identified new candidate genes (AQP1, DDX11, BAIAP2L1, and TMEM38B) by RNA sequencing of formalin-fixed, paraffin-embedded tissues and validating in frozen tissues [11].…”
Section: Introductionmentioning
confidence: 80%
“…We analyzed the expression of six genes (PBRM1, BAP1, SETD2, KDM5C, FOXC2, and CLIP4) reportedly associated with ccRCC, and four genes (AQP1, DDX11, BAIAP2L1, and TMEM38B) from our previous RNA-seq analysis of aggressive ccRCC at the clinical T1 stage [11].…”
Section: Patients and Tissuesmentioning
confidence: 99%
“…Diameters of the primary tumors were obtained via CT imaging. We assessed the expression levels of six genes (PBRM1, BAP1, SETD2, KDM5C, FOXC2, and CLIP4) reportedly associated with ccRCC, and four genes (AQP1, DDX11, BAIAP2L1, and TMEM38B) examined in our previous study involving RNA-seq analysis of aggressive ccRCC in clinical T1 stage [16,17].…”
Section: Patients and Tissuesmentioning
confidence: 99%
“…Previously, we found that several potential prognostic biomarkers are considerably up-or downregulated in ccRCC, and can be used to identify the aggressive clinical T1-stage [16,17]. In this study, we aimed to determine the association between visceral adiposity and the mRNA expression of potential biomarkers using frozen tumor tissues and preoperative plasma of patients with small ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-node-metastasis stage and pathological grade are generally adopted to estimate the risk of tumor recurrence in patients with ccRCC after surgical operation. Nevertheless, distinct outcomes are demonstrated in patients with equivalent tumor-node-metastasis stage and pathological grade ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%